Strategi Komunikasi Oza Rangkuti Dalam Meningkatkan Personal Branding @Podcastkeselaje - Pratiwia, Adinda Nurul; Utama, Dedy Kusna; Ekasari, Retno (LUGAS Jurnal Komunikasi, 2023)
The concept of personal branding involves creating and maintaining a positive public perception of oneself. This study aimed to examine Oza Rangkuti's communication strategy for improving their personal branding on TikTok, where they have 1.5 million followers and create content on South Jakarta language terms. The study employed a descriptive qualitative approach and utilized interviews, observation, and documentation as data collection techniques. Results revealed that Oza Rangkuti’s implemented the concept from Regina Luttrell's communication strategy on social media, which involves aspect sharing content on other social media platforms to attract more followers and keep them updated. Then, aspects optimize interactions with other users by responding to messages and comments, aspects manage their accounts by monitoring conversations and aspects engage, Oza to create content with other content creators to benefit both parties. Oza Rangkuti's personal branding was successful based on the characteristics, relevance, and consistency aspects of McNally & Speak's framework. Oza linked his content to events or issues in South Jakarta, made it relevant to everyday life, and consistently uploaded content twice a week for over a year.